Financial Availability on Performance of MSMEs: Mediation of Entrepreneurial Orientation and Business Actor's Rationality - maesaroh, Syti sarah; Rahayu, Agus; Wibowo, Lili Adi; Ahman, Eeng (Jurnal Economia, 2023)
This study investigates how business actors' entrepreneurial orientation and rationality affect MSMEs' performance, as well as how the availability of financing affects that performance. Using a random sampling technique, we surveyed 195 MSMEs from various business fields. The data were analyzed using structural equation modeling and AMOS and SPSS software. We discovered that the mediation of entrepreneurial orientation and decision-making rationality significantly impacted the relationship between financial availability and performance. Adequate funding encourages an entrepreneurial mindset and the development of innovations that improve overall performance. The study suggests that business actors improve their capabilities, including managerial skills, practices, and procedures in the financial sector. When adequate funds are available, they could be used to improve performance. The study adds to the dynamic capability theory by demonstrating that MSMEs must be able to integrate, construct, and reconfigure their financial resources in the face of rapid environmental changes.